Feedlot performance by month in Kansas - Ames, D.R. (Kansas State University. Agricultural Experiment Station, 2011)
Feedlot data on 202 lots involving approximately 40,000 steers collected for five years were used to characterize feedlot performance each month of the year. Intake, average daily gain (ADG), and feed efficiency were measured. ADG was predicted for mean daily temperature (MDT).
1776-1976 "Buffalo to Beef" is known as Cattlemen’s Day, 1976
Keywords: Beef; Feedlot performance; Average daily gain; Intake; Feed efficiency